A map matching approach for train positioning. Part II: Application and Experimentation - Saab, Samer S. (2000)
For pt.I see ibid., vol.49, no.2, p.467-75 (2000). In this paper, applications of the map matching algorithm proposed in part I are presented. In particular, steady-state Kalman filters are proposed and applied for filtering the yaw rate and tachometer signals. In addition, experimental results, using a quartz yaw rate sensor and axle encoders aboard a freight train, are included to show the performance of the proposed map matching algorithm.